STUDI KOMPARASI PERSEPSI KEMANFAATAN DAN KEMUDAHAN PENGGUNAAN APLIKASI MOBILE BANKING ANTARA GENERASI X, GENERASI Y, DAN GENERASI Z (Studi pada pengguna layanan mobile banking BCA di Kota Surakarta) - Ari Priyani; Siti Maryam; Burhanudin Ahmad Yani (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine differences in perceptions of usefulness and convenience between users of the BCA mobile banking application service in Generation X, Generation Y, and Generation Z. The samples used in the study were 90 respondents. In this study the method of sampling using accidental sampling which is a procedure based on accidental sampling. Data obtained directly by researchers from respondents' answers through a questionnaire consisting of several questions regarding the perception of use through the variable perceived usefulness and perceived ease of use. Based on the results of research conducted to users of BCA mobile banking services in generation X, generation Y, and generation Z in the city of Surakarta, it can be concluded that there is no significant difference in the perception variable benefits of the use of BCA mobile banking services in the city of Surakarta in the X generation , generation Y and generation Z, There is no significant difference in the perceived ease of use of the BCA mobile banking service in Surakarta in X generation, Y generation, and Z generation. Keywords: Usability, Ease, Mobile Banking, Generation